Increasing Production Capacyty And Efficiency Of Fruit Juice And Beverage Small Medium Enterprisess - Arie Febrianto Mulyadi (Journal of Innovation and Applied Technology, 2015)
ABSTRACT In Batu, 2 SMEs which produce fruit drink and beverage. SMEs "Sumber Barokah", producies strawberry and mulberry juice beverage with the brand "Arohmah" and SMEs "Tiga Bersaudara" Pepino juice products under the brand Nature Fresh. The current problems faced by SMEs is limited due to low production capacity capability (process capability) and the efficiency of production with production facilities still manually so that the quality and quantity of the product can not be maximal. Solutions from this activity was facilitation of the production machine semi-automatic cup sealer and Training and coaching of management of a commercial venture with the implementation of logbook, improved on-line marketing strategy serta Good Manufacturing Practices (GMP). The results showed an increase in production efficiency with a shorter time, production capacity and product quality improved so that it can meet consumer demand. Keywords: fruit drink and beverage, muelberry, production capacity, production efficiency, strawberry